Iron homeostasis, complement, and coagulation cascade as CSF signature of cortical lesions in early multiple sclerosis. Issue 11 (1st November 2019) - Magliozzi, Roberta; Hametner, Simon; Facchiano, Francesco; Marastoni, Damiano; Rossi, Stefania; Castellaro, Marco; Poli, Alberto; Lattanzi, Federico; Visconti, Andrea; Nicholas, Richard; Reynolds, Richard; Monaco, Salvatore; et al.
Abstract: Objective: Intrathecal inflammation, compartmentalized in cerebrospinal fluid (CSF) and in meningeal infiltrates, has fundamental role in inflammation, demyelination, and neuronal injury in cerebral cortex in multiple sclerosis (MS). Since the exact link between intrathecal inflammation and mechanisms of cortical pathology remains unknown, we aimed to investigate a detailed proteomic CSF profiling which is able to reflect cortical damage in early MS. Methods: We combined new proteomic method, TRIDENT, CSF analysis, and advanced 3T magnetic resonance imaging (MRI), in 64 MS patients at the time of diagnosis and 26 controls with other neurological disorders. MS patients were stratified according to cortical lesion (CL) load. Results: We identified 227 proteins differently expressed between the patients with high and low CL load. These were mainly related to complement and coagulation cascade as well as to iron homeostasis pathway (30 and 6% of all identified proteins, respectively). Accordingly, in the CSF of MS patients with high CL load at diagnosis, significantly higher levels of sCD163 ( P < 0.0001), free hemoglobin (Hb) ( P < 0.05), haptoglobin ( P < 0.0001), and fibrinogen ( P < 0.01) were detected. By contrast, CSF levels of sCD14 were significantly ( P < 0.05) higher in MS patients with low CL load. Furthermore, CSF levels of sCD163 positively correlated ( P < 0.01) with CSF levels of neurofilament, fibrinogen, and B cell‐related molecules, such as CXCL13, CXCL12, IL10, and BAFF. Interpretation: Intrathecal dysregulation of iron homeostasis and coagulation pathway as well as B‐cell and monocyte activity are strictly correlated with cortical damage at early disease stages.